Electrode plate, preparation method thereof and secondary battery

By using a first conductive agent containing a metal fiber matrix in the electrode sheet of the lithium-ion battery, combined with the second conductive agent and the second binder, the problems of low energy density, high safety risks and poor circulation performance of the existing lithium-ion battery are solved, and higher dynamic performance and circulation stability are achieved.

CN119673943APending Publication Date: 2025-03-21NIO BATTERY TECH (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311218837.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The energy density of existing lithium-ion batteries is close to the limit, and high-nickel ternary materials poses safety risks. The first charging efficiency of silicon negative electrode materials is low, short cycle life and cyclic expansion problems. The thick electrode plate technology leads to slow dynamics, high internal resistance, poor power performance and insufficient cycle life.

Method used

Using the first conductive agent containing the metal fiber matrix, an electrode sheet with excellent conductivity and reduced lithium ion transmission resistance is formed by improving the electron conductivity and shortening the electron and lithium ion transmission paths, and combining the second conductive agent and the second binder.

Benefits of technology

It significantly improves the dynamic performance of the electrode plate, reduces the polarization of the battery during the charging and discharging process, improves the battery's magnification and cycling performance, and solves the problems of insufficient dynamics, high internal resistance and short cycle life in thick electrode plate technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673943A_ABST
    Figure CN119673943A_ABST
Patent Text Reader

Abstract

The invention provides an electrode plate, a preparation method thereof, a secondary battery and a device. The electrode plate comprises a current collector and an active material layer, the active material layer is arranged on the current collector, the active material layer comprises an active material and a first conductive agent, and the first conductive agent comprises a metal fiber matrix and a carbon layer coating the surface of the metal fiber matrix. Therefore, through the synergistic effect of the metal fiber matrix and the carbon layer, the dynamic performance of the electrode plate can be remarkably improved, the polarization of the battery in the charging and discharging process is reduced, and the rate and cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of energy storage materials, and in particular to an electrode plate and a preparation method thereof, and a secondary battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, good power performance, and long cycle life. They have been increasingly used in the field of electric vehicles in recent years. In order to increase driving range, electric vehicles have an increasingly higher demand for the energy density of lithium batteries, which brings great opportunities and challenges to lithium-ion batteries.

[0003] In order to improve the energy density of lithium batteries, the method generally adopted by battery manufacturers in the past is to continuously upgrade the material system and adopt higher capacity positive and negative electrode materials. For example, the positive electrode ternary materials continue to develop towards high nickel positive electrodes, while the negative electrode materials gradually use silicon negative electrodes. Through the iteration of materials, the energy density of lithium batteries is continuously improved. However, as the current chemical system has almost reached the limit of battery energy density, the safety risk of using high nickel ternary materials is high, and the silicon negative electrode has problems such as low first charge efficiency, short cycle life and cycle expansion.

[0004] Therefore, the current electrode plates and their preparation methods, as well as secondary batteries, still need to be improved. Summary of the invention

[0005] In response to the problems existing in the existing technology, battery manufacturers have turned to seek breakthroughs in battery cell design and technology to further improve energy density, such as using thick electrode plate technology (i.e. increasing the coating amount of active material on the surface of the plate, and increasing the proportion of active materials in the electrode plate to improve the energy density of the battery). However, in the application of thick electrode plates, the thickness of the plate is greatly increased, resulting in very slow dynamics of the electrode plate; and after the thick plate is made into a battery, there are problems such as high internal resistance, poor power performance and insufficient cycle life. In addition, there are also some processing problems in the process processing, such as insufficient stripping force of the plate and powder loss. Therefore, how to effectively solve the problems encountered in the application of thick electrode plate technology and reduce the polarization of the battery while improving the energy density of the battery has become a hot topic in the battery field. The present disclosure provides a first conductive agent containing a metal fiber matrix, which has excellent conductivity and the ability to reduce lithium ion transmission resistance by improving electronic conductivity and shortening the electron and lithium ion transmission path; in the electrode plate, the first conductive agent is used in combination with a second conductive agent and a second binder, which can well solve the problem of insufficient dynamics of thick electrode plates in lithium batteries, reduce the electrode plate impedance as a whole, and improve the battery power performance and cycle performance.

[0006] The present disclosure provides an electrode plate, which includes: a current collector and an active material layer, wherein the active material layer is arranged on the current collector, the active material layer includes an active material and a first conductive agent, and the first conductive agent includes a metal fiber matrix and a carbon layer coated on the surface of the metal fiber matrix.

[0007] The present disclosure provides a method for preparing an electrode plate, comprising: mixing a first solvent with an active material, a first conductive agent, a second conductive agent, and a second binder to form a mixed slurry; wherein the first conductive agent comprises a metal fiber matrix and a carbon layer coated on the surface of the metal fiber matrix; forming the mixed slurry on a current collector, and forming the electrode plate through a drying process.

[0008] The present disclosure provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte; wherein the positive electrode is selected from the above-mentioned electrode sheet or the electrode sheet prepared according to the above-mentioned method.

[0009] The present disclosure provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte; wherein the negative electrode sheet is selected from the aforementioned electrode sheet or the electrode sheet prepared according to the aforementioned method.

[0010] Beneficial effects:

[0011] In the present disclosure, the first conductive agent of the electrode plate utilizes the excellent electron conductivity of the metal fiber matrix, thereby reducing the electron transfer resistance of the electrode plate, which is beneficial to the rapid transfer of electrons generated in the electrochemical reaction to the collector for conduction; in addition, since the diameter of the metal fiber matrix is ​​small and the ratio of length to diameter is large, it has good flexibility and the ability to construct a microscopic three-dimensional skeleton. On the one hand, it can enhance the conductive network bonding between the first conductive agent and the second conductive agent, thereby reducing the electron transfer resistance of the electrode plate; on the other hand, it can enhance the bonding ability between the active material and the metal fiber matrix through cooperation with the second binder, thereby improving the overall conductivity and processing performance of the electrode plate.

[0012] In the present disclosure, after the first conductive agent is introduced into the electrode plate, the first conductive agent will construct a three-dimensional network skeleton in the plate, and the three-dimensional network can divide the plate into multiple small areas. The electrons gained and lost by the active material in each small area in the electrochemical reaction can be transferred to the adjacent first conductive agent through the second conductive agent in the plate, and then the electrons are quickly transferred to the current collector through the metal fiber matrix in the first conductive agent. In the traditional plate structure, the active material in the plate can only gain and lose electrons through the traditional second conductive agent between particles. After using the first conductive agent, the rate of electron transfer can be significantly improved, and the electronic resistance can be reduced. The improvement is very obvious for thick electrode plates.

[0013] In the present disclosure, the carbon layer in the first conductive agent can increase the affinity of the first conductive agent to the electrolyte, thereby improving the liquid absorption and retention capabilities, and improving the wetting ability and lithium ion transmission capacity of the electrode plate; in addition, the carbon layer can also effectively reduce the impedance of the interface where the metal fiber matrix is ​​in direct contact with the active material, thereby improving the overall dynamic performance of the electrode plate.

[0014] In the present disclosure, the first conductive agent arranged perpendicular to the current collector in the electrode sheet, combined with the abundant electrolyte on the path, forms a rapid diffusion channel for lithium ions. Compared with traditional electrode sheets, the pore tortuosity of the electrode sheet can be reduced, the diffusion distance of lithium ions can be shortened, and the diffusion rate of lithium ions can be increased.

[0015] In the present disclosure, through the synergistic effect of the metal fiber matrix and the conductive carbon layer, the dynamic performance of the electrode plate can be significantly improved, the polarization of the battery during the charge and discharge process can be reduced, and the rate and cycle performance of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The schematic diagram of the structure of the first conductive agent prepared according to Example 1 is shown;

[0017] Figure 2 A schematic structural diagram of a positive electrode sheet prepared according to Example 1 is shown.

[0018] Description of reference numerals:

[0019] 1: first conductive agent with a longer length; 2: carbon layer coated on the surface of metal fiber matrix; 3: first conductive agent with a shorter length; 4: metal fiber matrix; 5: vertical rapid diffusion channel for lithium ions; 6: first conductive agent; 7: current collector. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present disclosure. The embodiments of the present disclosure should not be interpreted as limiting the present disclosure.

[0021] the term:

[0022] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0023] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.

[0024] In this document, it is necessary to understand that the orientations or positional relationships indicated by terms such as “upper”, “lower”, “top”, “bottom”, “inside” and “outside” are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention and simplifying the description. They do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0025] In the description herein, unless otherwise specified, “above” and “below” include the number.

[0026] Unless otherwise specified, the terms used in this disclosure have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this disclosure).

[0027] The term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values ​​are sometimes presented in this article in a range format. Such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values ​​explicitly designated as range limits, but also all individual numerical values ​​or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.

[0028] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0029] The present disclosure is further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.

[0030] Electrode plate:

[0031] The present invention provides an electrode plate, which includes a current collector and an active material layer, wherein the active material layer is arranged on the current collector, the active material layer includes an active material and a first conductive agent, and the first conductive agent includes a metal fiber matrix and a carbon layer coated on the surface of the metal fiber matrix.

[0032] Thus, the first conductive agent of the electrode plate utilizes the excellent electron-conducting ability of the metal fiber matrix, thereby reducing the electron transfer resistance of the electrode plate, which is conducive to the rapid transfer of electrons generated in the electrochemical reaction to the current collector for export; in addition, since the metal fiber matrix has a small diameter and a large ratio of length to diameter, it has good flexibility and the ability to construct a microscopic three-dimensional skeleton, which can enhance the conductive network combination of the first conductive agent and the second conductive agent on the one hand, and reduce the electron transfer resistance of the electrode plate; on the other hand, it can enhance the bonding ability of the active material and the metal fiber matrix through cooperation with the second binder, thereby improving the overall conductivity and processing performance of the electrode plate. After the first conductive agent is introduced into the electrode plate, the first conductive agent will construct a three-dimensional network skeleton in the plate, which can divide the plate into multiple small areas, and the electrons gained and lost by the active material in each small area in the electrochemical reaction can be transferred to the adjacent first conductive agent through the second conductive agent in the plate, and then the electrons are quickly transferred to the current collector through the metal fiber matrix in the first conductive agent. In the traditional electrode structure, the active material in the electrode can only gain or lose electrons through the traditional second conductive agent (such as natural graphite, artificial graphite, conductive carbon black) between particles. After using the first conductive agent, the rate of electron transfer can be significantly improved, and the electronic resistance can be reduced. The improvement is very obvious for thick electrode plates. The carbon layer in the first conductive agent can improve the affinity of the first conductive agent to the electrolyte, thereby improving the liquid absorption and retention capabilities, improving the wettability and lithium ion transmission capabilities of the electrode plate; in addition, the carbon layer can also effectively reduce the impedance of the interface where the metal fiber matrix is ​​in direct contact with the active material, thereby improving the overall dynamic performance of the electrode plate. The first conductive agent arranged perpendicular to the current collector in the electrode plate, combined with the abundant electrolyte on the path, forms a rapid diffusion channel for lithium ions. Compared with traditional electrodes, it can reduce the pore tortuosity of the electrode plate, shorten the distance of lithium ion diffusion, and increase the lithium ion diffusion rate. Through the synergistic effect of the metal fiber matrix and the conductive carbon layer, the dynamic performance of the electrode plate can be significantly improved, the polarization of the battery during the charge and discharge process can be reduced, and the battery rate and cycle performance can be improved.

[0033] In some embodiments, the specific structure of the carbon layer coated on the surface of the metal fiber matrix is ​​not particularly limited, as long as it can cover at least a portion of the surface of the metal fiber matrix. For example, the carbon layer coated on the surface of the metal fiber matrix can be in a discrete island form, or in a partially continuous layered form. The carbon layer coated on the surface of the metal fiber matrix can be firmly combined with the metal fiber matrix.

[0034] In some embodiments, the average diameter of the metal fiber matrix is ​​0.5 μm to 2 μm. Specifically, the average diameter of the metal fiber matrix is ​​0.5 μm, 0.7 μm, 0.9 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm or any value therebetween.

[0035] In some embodiments, the ratio of the length of the metal fiber matrix to the average diameter of the metal fiber matrix is ​​10 to 200. Specifically, the ratio of the length of the metal fiber matrix to the average diameter of the metal fiber matrix is ​​10, 20, 40, 60, 80, 100, 120, 140, 160, 180, 200 or any value therebetween.

[0036] In some embodiments, the metal fiber matrix includes at least one of aluminum, copper, silver, nickel, and titanium.

[0037] In some embodiments, the thickness of the carbon layer is 0.1 μm to 1 μm. Specifically, the thickness of the carbon layer is 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm or any value therebetween.

[0038] In some embodiments, the carbon layer includes a mixture of a first binder and at least one material selected from conductive carbon black and carbon nanotubes, wherein the first binder includes at least one of polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, polyacrylate, polyimide, polyvinylidene fluoride and polytetrafluoroethylene. The first binder acts between the metal fiber matrix and the particles in the carbon layer (at least one of the conductive carbon black and carbon nanotubes), and between the particles in the carbon layer, so that the particles in the carbon layer are firmly bound to the surface of the metal fiber matrix to maintain structural integrity.

[0039] In some embodiments, the carbon layer includes a first binder, conductive carbon black and carbon nanotubes. In some embodiments, the carbon layer includes a first binder, conductive carbon black and carbon nanotubes, based on the mass of the carbon layer, the mass percentage of the first binder is 10% to 40%, the mass percentage of the conductive carbon black is 55% to 70%, and the mass percentage of the carbon nanotubes is 5% to 20%. In some embodiments, based on the mass of the carbon layer, the mass percentage of the first binder is 10%, 15%, 20%, 25%, 30%, 35%, 40% or any value therebetween, the mass percentage of the conductive carbon black is 55%, 57%, 59%, 60%, 62%, 64%, 68%, 70% or any value therebetween, and the mass percentage of the carbon nanotubes is 5%, 7%, 9%, 10%, 12%, 14%, 16%, 18%, 20% or any value therebetween.

[0040] In some embodiments, the mass ratio of the metal fiber matrix to the carbon layer is 1:(0.1-1). Specifically, the mass ratio of the metal fiber matrix to the carbon layer is 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or any value therebetween.

[0041] In some embodiments, the mass percentage of the active material is 60% to 98% based on the total mass of the active material layer. Specifically, the mass percentage of the active material is 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 98% or any value therebetween based on the total mass of the active material layer.

[0042] In some embodiments, the mass percentage of the first conductive agent is 0.2% to 0.9% based on the total mass of the active material layer. Specifically, the mass percentage of the first conductive agent is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or any value therebetween based on the total mass of the active material layer.

[0043] In some embodiments, the active material layer also includes a second binder. In some embodiments, the second binder includes at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon. In some embodiments, based on the total mass of the active material layer, the mass percentage of the second binder is 0.5% to 2.0%. Specifically, based on the total mass of the active material layer, the mass percentage of the second binder is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0% or any value therebetween.

[0044] In some embodiments, the active material layer further includes a second conductive agent. In some embodiments, the second conductive agent includes at least one of a carbon-based material, a metal-based material, and a conductive polymer. The carbon-based material includes at least one of natural graphite, artificial graphite, conductive carbon black, acetylene black, Ketjen black, and carbon fiber, the metal-based material includes at least one of copper, nickel, aluminum, and silver, and the conductive polymer includes a polyphenylene derivative. In some embodiments, based on the total mass of the active material layer, the mass percentage of the second conductive agent is 0.3% to 1.6%. Specifically, based on the total mass of the active material layer, the mass percentage of the second conductive agent is 0.3%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, or any value therebetween.

[0045] In some embodiments, the type of active material is a positive electrode active material or a negative electrode active material.

[0046] In some embodiments, when the type of active material is a positive electrode active material, the electrode plate is a positive electrode plate, the positive electrode plate includes a current collector and a positive electrode active material layer, the positive electrode active material layer is arranged on the current collector, the positive electrode active material layer includes the positive electrode active material and a first conductive agent, the first conductive agent includes a metal fiber matrix and a carbon layer coated on the surface of the metal fiber matrix.

[0047] In some embodiments, when the type of active material is a positive electrode active material, the positive electrode active material includes at least one of a lithium nickel transition metal oxide and a phosphate.

[0048] In some embodiments, the lithium nickel transition metal oxide comprises LiNi x Co y M (1-x-y) O2, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1. In some embodiments, x is 0.5, 0.6, 0.7, 0.8, 0.9, 1 or any value therebetween. In some embodiments, y is 0.1, 0.2, 0.3, 0.4, 0.5 or any value therebetween. In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide and lithium nickel manganese oxide. In some embodiments, the positive electrode active material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92 and Ni95.

[0049] In some embodiments, the phosphate comprises LiMnk B (1-k) PO4, 0≤k≤1, B element includes at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead. In some embodiments, k is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or any value therebetween. In some embodiments, the phosphate includes at least one of lithium iron phosphate and lithium manganese iron phosphate. In some embodiments, the phosphate includes LiMn 0.6 Fe 0.4 PO4 and LiMn 0.8 Fe 0.2 At least one of PO4.

[0050] In some embodiments, when the type of active material is a positive electrode active material, the metal fiber matrix includes at least one of aluminum, silver, nickel, and titanium.

[0051] In some embodiments, when the type of active material is a positive electrode active material, the current collector includes aluminum.

[0052] In some embodiments, the positive electrode plate involved in the present disclosure is a thick electrode plate. For a battery made of a conventional current collector, the thickness of the single-sided positive electrode material layer is generally 60 to 100 μm; the thick electrode plate involved in the present disclosure refers to an electrode plate whose material layer thickness is greater than the thickness of conventional active materials.

[0053] In some embodiments, the positive active material may have a coating on the surface, or may be mixed with another compound having a coating. In some embodiments, the coating may include at least one coating element compound selected from an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound used for the coating may be amorphous or crystalline. The coating element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating may be applied by any method as long as the method does not adversely affect the performance of the positive active material. For example, the method may include any coating method well known to those of ordinary skill in the art, such as spraying, dipping, etc.

[0054] In some embodiments, the second conductive agent is selected from a combination of the first binder, conductive carbon black, and carbon nanotubes.

[0055] In some embodiments, when the type of active material is a negative electrode active material, the electrode plate is a negative electrode plate, the negative electrode plate includes a current collector and a negative electrode active material layer, the negative electrode active material layer is arranged on the current collector, the negative electrode active material layer includes a negative electrode active material and a first conductive agent, the first conductive agent includes a metal fiber matrix and a carbon layer coated on the surface of the metal fiber matrix.

[0056] In some embodiments, when the type of active material is a negative electrode active material, the negative electrode active material includes a silicon-based material, or a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium. In some embodiments, the silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound, and a silicon-carbon compound. In some embodiments, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. In some embodiments, the tin-based material includes at least one of tin, tin oxide, and a tin alloy. In some embodiments, the phosphorus-based material includes phosphorus and / or a phosphorus-carbon composite. In some embodiments, based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 10% to 100%. In some embodiments, based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, or any value therebetween.

[0057] In some embodiments, when the type of active material is a negative electrode active material, the metal fiber matrix includes at least one of copper, silver, nickel, and titanium.

[0058] In some embodiments, when the type of active material is a negative electrode active material, the current collector includes copper.

[0059] In some embodiments, when the type of active material is a negative electrode active material, the active material layer further includes a thickener, and the thickener includes at least one of sodium carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polyanionic cellulose, sodium polyanionic cellulose, polyacrylic acid, sodium polyacrylate, polyacrylate, konjac glucomannan, modified diatomaceous earth and sodium alginate.

[0060] In some embodiments, the mass percentage of the thickener is 0.3% to 1.0% based on the total mass of the active material layer. In some embodiments, the mass percentage of the thickener is 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% or any value therebetween based on the total mass of the active material layer.

[0061] In some embodiments of the present disclosure, the negative electrode plate involved in the present disclosure is a thick electrode plate. For a battery made of a conventional current collector, the thickness of the single-sided negative electrode active material is generally 50 μm to 100 μm; the thick electrode plate involved in the present disclosure refers to an electrode plate whose material layer thickness is greater than the thickness of the conventional active material.

[0062] Method for preparing electrode sheet

[0063] In the present disclosure, a method for preparing the aforementioned electrode sheet is provided. The electrode sheet prepared by the method may be the electrode sheet described above, and thus has all the features and advantages of the electrode sheet described above. The preparation method comprises:

[0064] S100: Mixing a first solvent with an active material, a first conductive agent, a second conductive agent, and a second binder to form a mixed slurry; wherein the first conductive agent includes a metal fiber matrix and a carbon layer coated on the surface of the metal fiber matrix.

[0065] S200: forming the mixed slurry on the current collector and forming an electrode plate through a drying process.

[0066] In some embodiments, the first conductive agent is formed by the following steps: mixing a second solvent, a carbon layer precursor material, and a first binder to form a carbon-containing slurry, wherein the carbon layer precursor material includes at least one of conductive carbon black and carbon nanotubes; coating the carbon-containing slurry on the surface of the metal fiber substrate, and drying to form the first conductive agent. The coating method is not particularly limited, and can be, for example, brushing, spraying, or dipping.

[0067] In some embodiments, based on the total mass of the active material, the first conductive agent, the second conductive agent and the second binder, the mass percentage of the active material is 60% to 98%. Specifically, the mass percentage of the active material is 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 98% or any value therebetween.

[0068] In some embodiments, based on the total mass of the active material, the first conductive agent, the second conductive agent and the second binder, the mass percentage of the first conductive agent is 0.2% to 0.9%. Specifically, the mass percentage of the first conductive agent is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or any value therebetween.

[0069] In some embodiments, based on the total mass of the active material, the first conductive agent, the second conductive agent and the second binder, the mass percentage of the second conductive agent is 0.3% to 1.6%. Specifically, the mass percentage of the second conductive agent is 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6% or any value therebetween.

[0070] In some embodiments, based on the total mass of the active material, the first conductive agent, the second conductive agent and the second binder, the mass percentage of the second binder is 0.5% to 2.0%. Specifically, the mass percentage of the second binder is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0% or any value therebetween.

[0071] In some embodiments, the carbon layer precursor material includes conductive carbon black and carbon nanotubes, based on the total mass of the carbon layer precursor material and the first binder, the mass percentage of the conductive carbon black is 55% to 70%, the mass percentage of the carbon nanotubes is 5% to 20%, and the mass percentage of the first binder is 10% to 40%. In some embodiments, the carbon layer precursor material includes conductive carbon black and carbon nanotubes, based on the total mass of the carbon layer precursor material and the first binder, the mass percentage of the conductive carbon black is 55%, 57%, 59%, 60%, 62%, 64%, 68%, 70% or any value therebetween, the mass percentage of the carbon nanotubes is 5%, 7%, 9%, 10%, 12%, 14%, 16%, 18%, 20% or any value therebetween, and the mass percentage of the first binder is 10%, 15%, 20%, 25%, 30%, 35%, 40% or any value therebetween. The first binder acts between the metal fiber matrix and the particles in the carbon layer (at least one of conductive carbon black and carbon nanotubes), and between the particles in the carbon layer, so that the particles in the carbon layer are firmly bound to the surface of the metal fiber matrix to maintain structural integrity.

[0072] In some embodiments, the first binder includes at least one of polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, polyacrylate, polyimide, polyvinylidene fluoride, and polytetrafluoroethylene.

[0073] In some embodiments, the first solvent and the second solvent each independently include at least one of deionized water, N-methylpyrrolidone, N,N-dimethylformamide, ethanol, dimethyl carbonate, and acetone.

[0074] In some embodiments, the drying temperature is 80°C to 110°C, and the drying time is 2 hours to 12 hours. In some embodiments, the drying temperature is 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, or any value therebetween, and the drying time is 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, or any value therebetween.

[0075] Secondary battery

[0076] The present disclosure also provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte.

[0077] In some embodiments, the positive electrode sheet includes the aforementioned electrode sheet or the electrode sheet prepared according to the aforementioned preparation method. In some embodiments, the negative electrode sheet includes the aforementioned electrode sheet or the electrode sheet prepared according to the aforementioned preparation method. It should be noted that when the type of the aforementioned electrode sheet is a positive electrode sheet, the positive electrode sheet in the secondary battery is the aforementioned positive electrode sheet or the positive electrode sheet prepared according to the aforementioned preparation method. When the type of the aforementioned electrode sheet is a negative electrode sheet, the negative electrode sheet in the secondary battery is the aforementioned negative electrode sheet or the negative electrode sheet prepared according to the aforementioned preparation method.

[0078] In some embodiments, the secondary battery of the present disclosure is provided with a separator between the positive electrode sheet and the negative electrode sheet to prevent short circuit. The material and shape of the separator used in the device of the present disclosure are not particularly limited, and it can be any technology disclosed in the prior art.

[0079] In some embodiments, the separator includes a polymer or an inorganic substance, etc., formed of a material that is stable to the electrolyte of the present disclosure.

[0080] In some embodiments, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polypropylene / polyethylene / polypropylene three-layer film, polyethylene terephthalate and polyimide.

[0081] In some embodiments, the secondary battery of the present disclosure further includes an electrolyte.

[0082] In some embodiments, the electrolyte includes a lithium salt and a solvent.

[0083] In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), trifluorosulfonyl lithium (LiTf), bis(fluorosulfonyl)imide lithium (LiFSI), lithium trifluoromethanesulfonate, (trifluoromethylsulfonyl) (perfluorobutylsulfonyl) imide lithium (LiFNFSI), bis(trifluoromethylsulfonyl) imide lithium (LiTFSI), bis(pentafluoroethylsulfonic acid) imide lithium (LiBETI), bis(fluoromalonate) borate lithium (LiBFMB), bis(oxalatoborate) lithium (LiBOB), difluorooxalatoborate lithium (LiDFOB), difluorobis(oxalatophosphate) lithium and 4,5-dicyano-2-(trifluoromethyl) imidazole lithium (LiTDI) at least one. In some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium salt is 4% to 25%. In some embodiments, the mass percentage of lithium salt is 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value therebetween. In some embodiments, the mass percentage of lithium salt is 6% to 18%.

[0084] In some embodiments, the solvent can be selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE). In some embodiments, the mass percentage of the solvent is 40% to 80% based on the mass of the electrolyte. In some embodiments, the mass percentage of the solvent is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In some embodiments, the mass percentage of the solvent is 50% to 70%.

[0085] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance. In some embodiments, the additives include at least one of a cyclic carbonate containing a carbon-carbon double bond, a silyl-containing phosphate, a silyl-containing borate, a nitrile compound, and propanesulfonic acid pyridinium salt. In some embodiments, the additives include at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), succinonitrile, adiponitrile, glutaronitrile, and hexanetrinitrile. In some embodiments, the additive further comprises at least one of methylene disulfonate (MMDS), ethylene disulfonate, 1,3-propane sultone (PS), 1-propylene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), vinyl sulfate (DTD), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), ethylene sulfite (DTO), dimethyl sulfite (DMS) and diethyl sulfite (DES). In some embodiments, the mass percentage of the additive is 0.05% to 10% based on the mass of the electrolyte. In some embodiments, the mass percentage of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage of the additive is 0.1% to 5%.

[0086] In some embodiments of the present disclosure, the secondary ion battery involved in the present disclosure may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0087] In some embodiments, the present disclosure further provides a battery module. The battery module includes the above-mentioned secondary ion battery. The number of secondary batteries contained in the battery module of the present disclosure can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0088] In some embodiments, the present disclosure further provides a battery pack, which includes the above-mentioned battery module; the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0089] Device:

[0090] The present disclosure also provides a device comprising at least one of the above-mentioned secondary battery, battery module and battery pack.

[0091] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of lithium batteries, a battery pack or battery module may be used.

[0092] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0093] The present disclosure is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present disclosure and are not used to limit the scope of the present disclosure.

[0094] Examples and Comparative Examples

[0095] Example 1

[0096] (1) Preparation of the first conductive agent:

[0097] Aluminum metal fibers with an average diameter of 1 μm and an aspect ratio of 50 are selected; conductive carbon black, carbon nanotubes, and a first binder polyvinylidene fluoride (PVDF) are uniformly dispersed in a solvent N-methylpyrrolidone (NMP) to obtain a carbon-containing coating slurry; then, in an inert gas atmosphere, at 95° C.±5° C., the carbon-containing coating slurry is uniformly coated on the surface of the aluminum metal fiber, and dried for 6 hours±0.5 hours to obtain the first conductive agent of Example 1, as shown in Figure 1 As shown, the carbon layer thickness is 0.3 μm.

[0098] (2) Preparation of positive electrode sheet:

[0099] The positive electrode active material lithium nickel cobalt manganese oxide, the second binder polyvinylidene fluoride (PVDF), the second conductive agent SuperP (conductive carbon black) and the first conductive agent prepared above are mixed in a solvent N-methylpyrrolidone (NMP) according to a weight ratio of about 96.6:1.2:1.5:0.7, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to obtain a positive electrode sheet, such as Figure 2 As shown, the black spherical or elliptical substance in the figure is the positive electrode active material.

[0100] (3) Preparation of negative electrode sheet:

[0101] Artificial graphite, the second conductive agent Super P (conductive carbon black), the thickener sodium carboxymethyl cellulose (CMC), and the second binder styrene butadiene rubber (SBR) are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a negative electrode sheet.

[0102] (4) Preparation of lithium batteries:

[0103] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery, wherein the diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9 μm and a ceramic thickness of 2 μm; the electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, the lithium salt is selected from LiPF6, the concentration is 1.15 mol / L, and the conductivity of the electrolyte is 9.3 mS / cm.

[0104] Embodiment 2:

[0105] The steps of Example 2 are the same as those of Example 1, except that the aspect ratio of the aluminum metal fiber used in Example 2 is 100.

[0106] Embodiment 3:

[0107] The steps of Example 3 are the same as those of Example 1, except that the aspect ratio of the aluminum metal fiber used in Example 3 is 150.

[0108] Embodiment 4:

[0109] The steps of Example 4 are the same as those of Example 1, except that the aspect ratio of the aluminum metal fiber used in Example 3 is 200.

[0110] Embodiment 5:

[0111] The steps of Example 5 are the same as those of Example 3, except that the average diameter of the aluminum metal fiber used in Example 5 is 0.5 μm, and the aspect ratio remains unchanged.

[0112] Embodiment 6:

[0113] (1) Preparation of the first conductive agent:

[0114] Copper metal fibers with an average diameter of 1 μm and an aspect ratio of 150 are selected; conductive carbon black, carbon nanotubes, and a first binder (polyacrylic acid, styrene-butadiene rubber, and carboxymethyl cellulose) are uniformly dispersed in a solvent of deionized water to obtain a carbon-containing coating slurry; then, in an inert gas atmosphere, at 95°C±5°C, the carbon-containing coating slurry is uniformly coated on the surface of the copper metal fiber, and dried for 6 hours±0.5 hours to obtain the first conductive agent of Example 6, wherein the thickness of the carbon layer is 0.3 μm.

[0115] (2) Preparation of negative electrode sheet:

[0116] The negative electrode active material artificial graphite, the second binder polyvinylidene fluoride (PVDF), the thickener CMC, the second conductive agent Super P and the first conductive agent prepared above are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 96:1.5:1.0:1.0:0.5 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to obtain a negative electrode sheet.

[0117] (3) Preparation of positive electrode sheet:

[0118] The positive electrode active material lithium nickel cobalt manganese oxide, the second conductive agent Super P and the second binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96:2:2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to obtain a positive electrode sheet.

[0119] (4) Preparation of lithium batteries:

[0120] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery, wherein the diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9 μm and a ceramic thickness of 2 μm; the electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, the lithium salt is selected from LiPF6, the concentration is 1.15 mol / L, and the conductivity is 9.3 mS / cm.

[0121] Embodiment 7:

[0122] (1) Preparation of the first conductive agent:

[0123] Aluminum metal fibers and copper metal fibers with an average diameter of 1 μm and an aspect ratio of 150 are selected respectively; conductive carbon black, carbon nanotubes, and a first binder are evenly dispersed in a solvent to obtain a carbon-containing coating slurry; then, in an inert gas atmosphere, at 95°C±5°C, the carbon-containing coating slurry is evenly coated on the surface of the aluminum metal fibers and the copper metal fibers, and dried for 6 hours±0.5 hours to obtain the first conductive agent of Example 7, wherein the thickness of the carbon layer is 0.3 μm.

[0124] (2) Preparation of negative electrode sheet:

[0125] The negative electrode active material artificial graphite, the second binder polyvinylidene fluoride (PVDF), the thickener CMC, the second conductive agent Super P and the first conductive agent containing copper metal fibers prepared above are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 96:1.5:1.0:1.0:0.5 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to obtain a negative electrode sheet.

[0126] (3) Preparation of positive electrode sheet:

[0127] The positive electrode active material lithium nickel cobalt manganese oxide, the second binder polyvinylidene fluoride (PVDF), the second conductive agent SuperP and the first conductive agent containing aluminum metal fibers prepared above are mixed in a solvent N-methylpyrrolidone (NMP) according to a weight ratio of about 96.6:1.2:1.5:0.7, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a positive electrode sheet.

[0128] (4) Preparation of lithium batteries:

[0129] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery. The diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9μm and a ceramic thickness of 2μm. The electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, and the lithium salt is selected from LiPF6 with a concentration of 1.15mol / L and a conductivity of 9.3mS / cm.

[0130] Embodiment 8:

[0131] (1) Preparation of the first conductive agent:

[0132] Aluminum metal fibers with an average diameter of 1 μm and an aspect ratio of 150 are selected respectively; conductive carbon black, carbon nanotubes, and a first binder are evenly dispersed in a solvent to obtain a carbon-containing coating slurry; then, in an inert gas atmosphere, at 95°C±5°C, the carbon-containing coating slurry is evenly coated on the surface of the aluminum metal fiber, and dried for 6 hours±0.5 hours to obtain the first conductive agent of Example 8, wherein the thickness of the carbon layer is 0.3 μm.

[0133] (2) Preparation of negative electrode sheet:

[0134] The negative electrode active material artificial graphite, the second binder polyvinylidene fluoride (PVDF), the thickener CMC, and the second conductive agent Super P are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 96.5:1.5:1.0:1.0 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a negative electrode sheet.

[0135] (3) Preparation of positive electrode sheet:

[0136] The positive electrode active material lithium nickel cobalt manganese oxide, the second binder polyvinylidene fluoride (PVDF), the second conductive agent SuperP and the first conductive agent containing aluminum metal fibers prepared above are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96.8:1.2:1.5:0.5, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to obtain a positive electrode sheet.

[0137] (4) Preparation of lithium batteries:

[0138] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery. The diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9μm and a ceramic thickness of 2μm. The electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, and the lithium salt is selected from LiPF6 with a concentration of 1.15mol / L and a conductivity of 9.3mS / cm.

[0139] Embodiment 9:

[0140] (1) Preparation of the first conductive agent:

[0141] Aluminum metal fibers with an average diameter of 1 μm and an aspect ratio of 150 are selected respectively; conductive carbon black, carbon nanotubes, and a first binder are evenly dispersed in a solvent to obtain a carbon-containing coating slurry; then, in an inert gas atmosphere, at 95°C±5°C, the carbon-containing coating slurry is evenly coated on the surface of the aluminum metal fiber, and dried for 6 hours±0.5 hours to obtain the first conductive agent of Example 9, wherein the thickness of the carbon layer is 0.3 μm.

[0142] (2) Preparation of negative electrode sheet:

[0143] The negative electrode active material artificial graphite, the second binder polyvinylidene fluoride (PVDF), the thickener CMC, and the second conductive agent Super P are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 96.5:1.5:1.0:1.0 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a negative electrode sheet.

[0144] (3) Preparation of positive electrode sheet:

[0145] The positive electrode active material lithium nickel cobalt manganese oxide, the second binder polyvinylidene fluoride (PVDF), the second conductive agent SuperP and the first conductive agent containing aluminum metal fibers prepared above are mixed in a solvent N-methylpyrrolidone (NMP) according to a weight ratio of about 96.4:1.2:1.5:0.9, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to obtain a positive electrode sheet.

[0146] (4) Preparation of lithium batteries:

[0147] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery. The diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9μm and a ceramic thickness of 2μm. The electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, and the lithium salt is selected from LiPF6 with a concentration of 1.15mol / L and a conductivity of 9.3mS / cm.

[0148] Embodiment 10:

[0149] (1) Preparation of the first conductive agent:

[0150] Aluminum metal fibers with an average diameter of 2 μm and an aspect ratio of 150 are selected respectively; conductive carbon black, carbon nanotubes, and a first binder polyvinylidene fluoride are uniformly dispersed in a solvent to obtain a carbon-containing coating slurry; then, in an inert gas atmosphere, at 95°C±5°C, the carbon-containing coating slurry is uniformly coated on the surface of the aluminum metal fiber, and dried for 6 hours±0.5 hours to obtain the first conductive agent of Example 9, wherein the thickness of the carbon layer is 0.3 μm.

[0151] (2) Preparation of negative electrode sheet:

[0152] The negative electrode active material artificial graphite, the second binder polyvinylidene fluoride (PVDF), the thickener CMC, and the second conductive agent Super P are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 96.5:1.5:1.0:1.0 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a negative electrode sheet.

[0153] (3) Preparation of positive electrode sheet:

[0154] The positive electrode active material lithium nickel cobalt manganese oxide, the second binder polyvinylidene fluoride (PVDF), the second conductive agent SuperP and the first conductive agent containing aluminum metal fibers prepared above are mixed in a solvent N-methylpyrrolidone (NMP) according to a weight ratio of about 96.6:1.2:1.5:0.7, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a positive electrode sheet.

[0155] (4) Preparation of lithium batteries:

[0156] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery. The diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9μm and a ceramic thickness of 2μm. The electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, and the lithium salt is selected from LiPF6 with a concentration of 1.15mol / L and a conductivity of 9.3mS / cm.

[0157] Embodiment 11:

[0158] The steps of Example 11 are the same as those of Example 10, except that in Example 11, when preparing the first conductive agent:

[0159] Aluminum metal fibers with an average diameter of 1 μm and an aspect ratio of 150 are selected respectively; conductive carbon black, carbon nanotubes, and a first binder are evenly dispersed in a solvent to obtain a carbon-containing coating slurry; then, in an inert gas atmosphere, at 95°C±5°C, the carbon-containing coating slurry is evenly coated on the surface of the aluminum metal fiber, and dried for 6 hours±0.5 hours to obtain the first conductive agent of Example 11, wherein the thickness of the carbon layer is 0.1 μm.

[0160] Embodiment 12:

[0161] The steps of Example 12 are the same as those of Example 10, except that in Example 12, when preparing the first conductive agent:

[0162] Aluminum metal fibers with an average diameter of 1 μm and an aspect ratio of 150 are selected respectively; conductive carbon black, carbon nanotubes, and a first binder are evenly dispersed in a solvent to obtain a carbon-containing coating slurry; then, in an inert gas atmosphere, at 95°C±5°C, the carbon-containing coating slurry is evenly coated on the surface of the aluminum metal fiber, and dried for 6 hours±0.5 hours to obtain the first conductive agent of Example 12, wherein the thickness of the carbon layer is 1 μm.

[0163] Comparative Example 1:

[0164] (1) Preparation of positive electrode sheet:

[0165] The positive electrode active material lithium nickel cobalt manganese oxide, the second binder polyvinylidene fluoride (PVDF), and the second conductive agent SuperP are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96.6:1.2:2.2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a positive electrode sheet.

[0166] (2) Preparation of negative electrode sheet:

[0167] Artificial graphite, the second conductive agent Super P (conductive carbon black), the thickener sodium carboxymethyl cellulose (CMC), and the second binder styrene butadiene rubber (SBR) are fully stirred and mixed in a proper amount of deionized water solvent according to a weight ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain the negative electrode active material layer, and then cut, slit, and weld the pole ears to obtain the pole piece.

[0168] (3) Preparation of lithium batteries:

[0169] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery. The diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9μm and a ceramic thickness of 2μm. The electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, and the lithium salt is selected from LiPF6 with a concentration of 1.15mol / L and a conductivity of 9.3mS / cm.

[0170] Comparative Example 2:

[0171] (1) Preparation of the first conductive agent:

[0172] Aluminum metal fibers with an average diameter of 1 μm and an aspect ratio of 150 were selected.

[0173] (2) Preparation of negative electrode sheet:

[0174] The negative electrode active material artificial graphite, the second binder polyvinylidene fluoride (PVDF), the thickener CMC, and the second conductive agent Super P are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 96.5:1.5:1.0:1.0 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a negative electrode sheet.

[0175] (3) Preparation of positive electrode sheet:

[0176] The positive electrode active material lithium nickel cobalt manganese oxide, the second binder polyvinylidene fluoride (PVDF), the second conductive agent SuperP and aluminum metal fiber are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96.6:1.2:1.5:0.7, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to the pole ear to obtain a positive electrode sheet.

[0177] (4) Preparation of lithium batteries:

[0178] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery. The diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9μm and a ceramic thickness of 2μm. The electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, and the lithium salt is selected from LiPF6 with a concentration of 1.15mol / L and a conductivity of 9.3mS / cm.

[0179] Comparative Example 3:

[0180] (1) Preparation of the first conductive agent:

[0181] Copper metal fibers with an average diameter of 1 μm and an aspect ratio of 150 were selected.

[0182] (2) Preparation of negative electrode sheet:

[0183] The negative electrode active material artificial graphite, the second binder polyvinylidene fluoride (PVDF), the thickener CMC, the second conductive agent Super P and the copper metal fiber are fully stirred and mixed in an appropriate amount of deionized water solvent according to a weight ratio of 95.8:1.5:1.0:1.0:0.7 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector copper foil, dried and cold pressed to obtain a negative electrode active material layer, and then cut, slit and welded to obtain a negative electrode sheet.

[0184] (3) Preparation of positive electrode sheet:

[0185] The positive electrode active material lithium nickel cobalt manganese oxide, the second conductive agent Super P and the second binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of about 96:2:2, and stirred evenly to obtain a slurry. The slurry is coated on the positive electrode current collector aluminum foil, dried and cold pressed to obtain a positive electrode active material layer, and then cut, slit, and welded to obtain a positive electrode sheet.

[0186] (4) Preparation of lithium batteries:

[0187] The above positive and negative electrode sheets are subjected to processes such as rolling, die-cutting, lamination, and injection to be assembled into a battery, wherein the diaphragm adopts a double-sided ceramic diaphragm with a base film thickness of 9 μm and a ceramic thickness of 2 μm; the electrolyte adopts a solvent system of EC:DMC:EMC=2:3:5, the lithium salt is selected from LiPF6, the concentration is 1.15 mol / L, and the conductivity is 9.3 mS / cm.

[0188] Test Method

[0189] 1. Test of electrode peeling force:

[0190] The electrode adopts 180° peeling test. First, take the coated electrode and use a cutting knife to cut it into a size of 25mm×200mm in length and width. Take a 20mm wide double-sided tape and stick it on the surface of the steel plate. One end of the double-sided tape is flush with the bottom of the steel plate and centered. Stick the test electrode to the surface of the double-sided tape with the end face flush. Use a pressure wheel to roll back and forth on the surface of the electrode for more than 3 times. Fold the unpasted end of the test electrode 180° and clamp it in the upper clamp of the tensile machine. Clamp the steel plate in the lower clamp and perform a peeling test at 50mm / min. When the electrode coating is completely separated from the current collector, read the test result and take the stable stage of the test curve as the electrode peeling strength value.

[0191] 2. DCR impedance test:

[0192] The prepared lithium-ion battery was subjected to a discharge DCR test. The test process was to adjust the battery state to 50% SOC, then place it in a 25°C environmental chamber for more than 5 hours, use a 2C constant current pulse discharge for 10S, record the battery voltage (V1, V2) before and after discharge, and calculate the cell DCR by DCR = (V2-V1) / 2C.

[0193] 3. Fast charging cycle test:

[0194] The prepared lithium-ion battery was subjected to a fast charge cycle test. The test process was as follows: at room temperature, the battery was charged to 4.2V with a 2C constant current, then charged to 0.05C with a constant voltage, left for 30 minutes, and then discharged to 2.5V with a 1C constant current, left for 30 minutes. The above steps were repeated 10 times, and then the battery was fully charged and disassembled to confirm the interface status.

[0195] 4. Capacity retention rate test:

[0196] The battery cell is subjected to a capacity retention test, i.e., a cycle test. The test process is as follows: at room temperature, the battery is charged to 4.2V with a 1C constant current, then charged to 0.05C with a constant voltage, left for 30 minutes, and then discharged to 2.5V with a 1C constant current, then left for 30 minutes. The above steps are repeated, and the discharge capacity Cn of the battery cell is recorded each time. The initial capacity of the battery cell is recorded as C0. After repeating the above steps for 300 cycles of charge and discharge, the capacity of the battery cell is C300. The 300-week capacity retention rate of the battery cell is calculated by the formula = C300 / C0*100%.

[0197] Test results:

[0198] Examples 1 to 9 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1 below:

[0199] Table 1

[0200]

[0201] As can be seen from Table 1, by comparing Examples 1 to 12 with Comparative Examples 1 to 3, the first conductive agent of the electrode plate utilizes the excellent electron-conducting ability of the metal fiber matrix to reduce the electron transfer resistance of the electrode plate, that is, the impedance DCR is reduced, which is conducive to the rapid transfer of electrons generated in the electrochemical reaction to the collector for extraction; in addition, since the diameter of the metal fiber matrix is ​​small and the ratio of length to diameter is large, it has good flexibility and the ability to construct a microscopic three-dimensional skeleton. On the one hand, it can enhance the conductive network combination of the first conductive agent and the second conductive agent, and reduce the electron transfer resistance of the electrode plate; on the other hand, it can enhance the bonding ability of the active material and the metal fiber matrix by cooperating with the second binder, thereby improving the overall conductivity and processing performance of the electrode plate. Therefore, by adding the first conductive agent to the electrode plate, the present application can reduce the internal resistance of the battery cell, improve the stripping force of the plate, reduce the polarization of the battery during the charge and discharge process, and improve the rate and cycle performance of the battery.

[0202] According to Comparative Example 1, when the first conductive agent in the present application is not added to the electrode pole piece, the secondary battery impedance is large, the pole piece peeling force is relatively low, the battery polarization is severe during the charge and discharge process, and the battery cycle performance is poor. According to Comparative Examples 2 to 3, when only a metal fiber matrix is ​​added to the electrode pole piece, and the surface of the metal fiber matrix is ​​not coated with the carbon layer in the present application, the overall performance is slightly improved relative to Comparative Example 1, but compared with the embodiment, the secondary battery impedance is still large, the pole piece peeling force is relatively low, the battery polarization is severe during the charge and discharge process, and the battery cycle performance is poor.

[0203] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present disclosure, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present disclosure.

Claims

1. An electrode plate, characterized in that: include: current collector; An active material layer is disposed on the current collector, the active material layer comprises an active material and a first conductive agent, and the first conductive agent comprises a metal fiber matrix and a carbon layer coated on the surface of the metal fiber matrix.

2. The electrode plate according to claim 1, characterized in that: The carbon layer comprises a mixture of a first binder and at least one material selected from conductive carbon black and carbon nanotubes, wherein the first binder comprises at least one of polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, polyacrylate, polyimide, polyvinylidene fluoride and polytetrafluoroethylene; and / or The metal fiber matrix comprises at least one of aluminum, copper, silver, nickel and titanium; and / or The average diameter of the metal fiber matrix is ​​0.5 μm to 2 μm; and / or The ratio of the length of the metal fiber matrix to the average diameter of the metal fiber matrix is ​​10-200.

3. The electrode plate according to claim 2, characterized in that: The carbon layer comprises a first binder, conductive carbon black and carbon nanotubes, wherein based on the mass of the carbon layer, the mass percentage of the first binder is 10% to 40%, the mass percentage of the conductive carbon black is 55% to 70%, and the mass percentage of the carbon nanotubes is 5% to 20%; and / or The thickness of the carbon layer is 0.1 μm to 1 μm; and / or The mass ratio of the metal fiber matrix to the carbon layer is 1:(0.1-1); and / or Based on the total mass of the active material layer, the mass percentage of the active material is 60% to 98%, and the mass percentage of the first conductive agent is 0.2% to 0.9%.

4. The electrode plate according to claim 1, characterized in that: The active material layer further comprises: a second binder, wherein the second binder comprises at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin and nylon; the mass percentage of the second binder is 0.5% to 2.0% based on the total mass of the active material layer; and / or A second conductive agent, the second conductive agent includes at least one of a carbon-based material, a metal-based material and a conductive polymer, the carbon-based material includes at least one of natural graphite, artificial graphite, conductive carbon black, acetylene black, Ketjen black and carbon fiber, the metal-based material includes at least one of copper, nickel, aluminum and silver, and the conductive polymer includes a polyphenylene derivative; based on the total mass of the active material layer, the mass percentage of the second conductive agent is 0.3% to 1.6%.

5. The electrode plate according to claim 4, characterized in that: The type of the active material is a positive electrode active material, and the electrode plate satisfies at least one of the following conditions: (a) The positive electrode active material includes at least one of a lithium nickel transition metal oxide and a phosphate; the lithium nickel transition metal oxide includes LiNi x Co y M (1-x-y) O2, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1; the phosphate includes LiMnkB (1-k) PO4, 0≤k≤1, and the B element includes at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead; (b) the metal fiber matrix comprises at least one of aluminum, silver, nickel and titanium; (c) The current collector includes aluminum.

6. The electrode plate according to claim 4, characterized in that: The type of the active material is a negative electrode active material, and the electrode plate satisfies at least one of the following conditions: (d) the negative electrode active material comprises a silicon-based material, or a mixture of a silicon-based material and at least one material selected from a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium; the silicon-based material comprises at least one of silicon, a silicon alloy, a silicon oxide compound and a silicon carbon compound, the carbon-based material comprises at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, the tin-based material comprises at least one of tin, tin oxide and a tin alloy, and the phosphorus-based material comprises phosphorus and / or a phosphorus-carbon composite; based on the mass of the negative electrode active material, the mass percentage of the silicon-based material is 10% to 100%; (e) the metal fiber matrix comprises at least one of copper, silver, nickel and titanium; (f) the current collector comprises copper; (g) The active material layer also includes a thickener, and the thickener includes at least one of sodium carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polyanionic cellulose, sodium polyanionic cellulose, polyacrylic acid, sodium polyacrylate, polyacrylate, konjac glucomannan, modified diatomaceous earth and sodium alginate; based on the total mass of the active material layer, the mass percentage of the thickener is 0.3% to 1.0%.

7. A method for preparing an electrode sheet, characterized in that: include: Mixing a first solvent with an active material, a first conductive agent, a second conductive agent, and a second binder to form a mixed slurry; wherein the first conductive agent comprises a metal fiber matrix and a carbon layer coated on the surface of the metal fiber matrix; The mixed slurry is formed on a current collector and dried to form the electrode sheet.

8. The method according to claim 7, characterized in that The first conductive agent is formed by the following steps: Mixing a second solvent, a carbon layer precursor material and a first binder to form a carbon-containing slurry, wherein the carbon layer precursor material includes at least one of conductive carbon black and carbon nanotubes; The carbonaceous slurry is coated on the surface of the metal fiber substrate and dried to form the first conductive agent.

9. The method according to claim 8, characterized in that Based on the total mass of the active material, the first conductive agent, the second conductive agent and the second binder, the mass percentage of the active material is 60% to 98%, the mass percentage of the second conductive agent is 0.2% to 0.9%, the mass percentage of the second conductive agent is 0.3% to 1.6%, and the mass percentage of the second binder is 0.5% to 2.0%; and / or The carbon layer precursor material comprises conductive carbon black and carbon nanotubes, and based on the total mass of the carbon layer precursor material and the first binder, the mass percentage of the conductive carbon black is 55% to 70%, the mass percentage of the carbon nanotubes is 5% to 20%, and the mass percentage of the first binder is 10% to 40%; and / or The drying process is performed at a temperature of 80°C to 110°C for a period of 2 hours to 12 hours; and / or The first binder comprises at least one of polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, polyacrylate, polyimide, polyvinylidene fluoride and polytetrafluoroethylene; and / or The first solvent and the second solvent independently include at least one of deionized water, N-methylpyrrolidone, N,N-dimethylformamide, ethanol, dimethyl carbonate and acetone.

10. A secondary battery, characterized in that: Including positive electrode sheet, negative electrode sheet and electrolyte; Wherein, the positive electrode plate comprises the electrode plate according to any one of claims 1 to 5 or the electrode plate prepared by the method according to any one of claims 7 to 9; and / or The negative electrode plate comprises the electrode plate according to any one of claims 1 to 4 and 6 or the electrode plate prepared by the method according to any one of claims 7 to 9.